1998
DOI: 10.1021/cm970629+
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Speciation in Nanophase MgO from Solid-State 17O NMR

Abstract: Nanocrystalline MgO has been sol-gel manufactured to give a range of crystallite sizes from 1.8 to 35 nm as determined by powder X-ray diffraction. A multinuclear magnetic resonance approach using 13 C, 17 O, and 25 Mg provides information on the atomic scale structure. It is found that despite extensive hydrolysis that -CH 3 fragments persist until extensive calcination has been performed. In 17 O magic angle spinning NMR spectra three signals are detected that are assigned to MgO-like, a surface species, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
1
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 32 publications
5
51
1
2
Order By: Relevance
“…Hence, a decrease in the copper crystallite size results in a symmetric NMR line broadening, while an increase in strain or disorder causes an asymmetric NMR line profile. [9,24] Figure 12 shows the 63 Cu NMR spectra of the Cu/ZrO 2 catalyst after various reaction steps. Besides differences in the amplitude it can be seen, that the width of the NMR lines varies only slightly as a function of the treatment conditions.…”
Section: Nuclear Magnetic Resonance (Nmr) Spectroscopymentioning
confidence: 99%
“…Hence, a decrease in the copper crystallite size results in a symmetric NMR line broadening, while an increase in strain or disorder causes an asymmetric NMR line profile. [9,24] Figure 12 shows the 63 Cu NMR spectra of the Cu/ZrO 2 catalyst after various reaction steps. Besides differences in the amplitude it can be seen, that the width of the NMR lines varies only slightly as a function of the treatment conditions.…”
Section: Nuclear Magnetic Resonance (Nmr) Spectroscopymentioning
confidence: 99%
“…[68,69] Nanocrystalline MgO has been prepared by a variety of routes including sol-gel processing [8-11, 21, 66, 70, 71] and dehydration of the hydroxide. [72] These preparative methods have been followed by a variety of experimental techniques including X-ray crystallography (XRD), 13 C, 17 O and 25 Mg NMR [70] and Mg K-edge XAS [72] and show that careful calcinations are required to fully obtain nanocrystalline MgO. It has been shown that the catalyst used during the hydrolysis and condensation of magnesium methoxide plays a significant role in determining the nature of the material obtained at low calcination temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the catalyst used during the hydrolysis and condensation of magnesium methoxide plays a significant role in determining the nature of the material obtained at low calcination temperatures. [21] For example, it has been shown that the hydrolysis product of magnesium methoxide is Mg(OH)A C H T U N G T R E N N U N G (OCH 3 ), [70] and that calcination at temperatures greater than 500 8C are required to obtain MgO. [21,70] There is very little EXAFS data concerning MgO [72,73] due to the fact it is a light element.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11]). The main advantage of these methods is their ability to study local properties of the solids that is very important for nanomaterials, namely nanograin ceramics, nanoparticle powders, thin films.…”
Section: Introductionmentioning
confidence: 99%